Analisis Kadar Logam Timah (Sn), Kromium (Cr) dan Timbal (Pb) Pada Susu Kental Manis Kemasan Kaleng Dengan Spekrofotometri Serapan Atom - Subardi Bali; Deri Islami; Yurnaliza Yurnaliza (LPPM Universitas Abdurrab, 2025)
Sweetened condensed milk packaged in cans aims to extend the shelf life of the milk. Usually, the can components use tin as a steel coating, chromium as a tin coating, and lead to connect the lid and body so that it can be contaminated with heavy metals originating from the can components, therefore it is necessary to pay attention to the safety and its effects on packaged food. This study was conducted to determine the levels of tin (Sn), chromium (Cr), and lead (Pb) contained in canned sweetened condensed milk based on its production period and to determine the appropriateness of the levels of heavy metals contained in canned sweetened condensed milk. Samples of canned sweetened condensed milk were taken randomly in Pekanbaru city with 3 brands and different expiration dates. The samples were analyzed using Atomic Absorption Spectrophotometry. The concentration of tin metal in SKI samples ranged from 124.00 - 155.05 mg/kg, SKE samples ranged from 122.40 - 151.71 mg/kg and SKF samples ranged from 147.00 - 162.12 mg/kg. The concentration of chromium metal in SKI samples ranged from 0.33 - 0.55 mg/kg, SKE samples ranged from 0.32 - 0.44 mg/kg, and SKF samples ranged from 0.24 mg/kg. The concentration of lead metal in SKI milk ranged from 0.076-0.14 mg/kg, SKE samples ranged from 0.032-0.048 mg/kg and SKF samples ranged from 0.045-0.061 mg/kg. Based on the regulation of the Food and Drug Supervisory Agency number 9 of 2022 concerning the maximum limit of metal contamination in canned SKI milk products, canned SKI milk, and canned SKF milk are not suitable for consumption because all samples contain heavy metal contamination of chromium and lead that exceeds the threshold.